Comparison of Staple Food Availability in Urban and Rural Households in Kabupaten Malaka - Falentina Adriana Nahak; Johanna Suek; Lika Bernadina (Universitas Muhammadiyah Malang, 2021)
This study aims to investigate the differences staple food availability and household consumption patterns in urban and rural areas. This research took place in Kabupaten Malaka, with the sample of 60 urban households and 60 households chosen through random sampling. The obtianed data were analyzed qualitatively and quantitatively. Results show that staple food availability respondents’ household were from the production of own farming, purchasing, and assistance from relatives. However, the availability of staple food did not support household consumption needs for 365 days (1 year). Staple food availability index in urban areas was 58.4, and the rural households reached 57.2. These numbers were far below the national index of 100. Analysis of z-tests showed significant differences in staple food availability between urban and rural households.